The Impact of Highway Investment on Development - Wilson, George Wilton (Washington: Brookings Institution Transport Research Program, 1966)
This book sets out an empirical investigation of the actual impacts of specific transport investments at particular places and times using selected countries as a case study: The Cochabamba-Santa Cruz Highway in Bolivia, the Atlantic Highway in Guatemala, and the Littoral Highway in El-Salvador.
Bibliographical footnotes.
ne 22/02/2018
Loan
Keywords: Roads